Catostylus tagi: partial rDNA sequencing and characterisation of nematocyte structures using two improvements in jellyfish sample preparation - Parracho, Tiago (2015)
Artigo relacionado com a dissertação de mestrado disponível no Repositório da Egas Moniz em http://comum.rcaap.pt/handle/123456789/6259